1999
DOI: 10.1381/096089299765553539
|View full text |Cite
|
Sign up to set email alerts
|

The World's First Obesity Surgery Performed by a Surgeon at a Distance

Abstract: This procedure demonstrates that telesurgical procedures are feasible, can be performed safely even in obese patients, and improve the surgeon's comfort by restoring ergonomically acceptable conditions, by increasing the number of degrees of freedom, and by recreating the eye-hand connection lost in videoendoscopic procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
74
0
4

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(78 citation statements)
references
References 8 publications
0
74
0
4
Order By: Relevance
“…The first reports on the use of robotic technology in surgery encompassed the hybrid technique ("robot-assisted") where the robot was used in only part in the conventional laparoscopy, mainly in the anastomoses. The first robotic bariatric surgery took place in 1998, with the placement of a robot-assisted adjustable gastric band 8 . In 2003, in a series of 211 cases of robot-assisted surgeries, the authors reported seven RYGB, those been the first reports of this type of bariatric surgery with the help of robotics 28 .…”
Section: Discussionmentioning
confidence: 99%
“…The first reports on the use of robotic technology in surgery encompassed the hybrid technique ("robot-assisted") where the robot was used in only part in the conventional laparoscopy, mainly in the anastomoses. The first robotic bariatric surgery took place in 1998, with the placement of a robot-assisted adjustable gastric band 8 . In 2003, in a series of 211 cases of robot-assisted surgeries, the authors reported seven RYGB, those been the first reports of this type of bariatric surgery with the help of robotics 28 .…”
Section: Discussionmentioning
confidence: 99%
“…For that reason, adoption of robotic technology for this procedure is scarce. Nevertheless, Cadiere et al, described the first robotic gastric band placement in 1999 (Cadiere et al, 1999). Later, several studies in the literature have reported the use of robotics for LAGB (Edelson et al, 2011;Moser & Horgan, 2004).…”
Section: Robotic Gastric Adjustable Band Placementmentioning
confidence: 99%
“…This statistic can be explained by the small number of bariatric cases performed laparoscopically and by the limited number of institutions with a robotics system available for use. The first robot-assisted adjustable gastric banding was reported in 1999 (Cadiere et al, 1999), and Horgan and collaborators performed the first robot-assisted gastric bypass in September 2000 . Since that time there have been numerous publications detailing the use of robotic assistance in bariatric surgery.…”
Section: Introductionmentioning
confidence: 99%
“…En 1997 ya había iniciado sus experiencias con un sistema de cirugía robotizada mediante un prototipo llamado Mona, un robot precursor del actual da Vinci, que utilizaba ya un sistema amo-esclavo con consola de mandos y brazos independientes para que un cirujano, situado fuera del campo quirúrgico, comande los brazos robóticos colocados, mediante laparoscopia, en el interior del abdomen del paciente 43 . Con esta técnica se realizaron en Bélgica una colecistectomía (1997) y una cirugía bariátrica (1998), la primera en el mundo realizada por un robot dirigido a distancia 44 .…”
Section: Robots Quirúrgicosunclassified
“…En los 6 últimos años el robot se ha ido consolidando como el proyecto más avanzado en robótica quirúrgica, después de más de 25 años en desarrollo 43 . Desde 1997 se han ido realizando diversos procedimientos de cirugía abdominal como funduplicatura de Nissen-Rosetti 49 , miotomía de Heller 50 , plicatura gástrica 44 y anastomosis gastrointestinal tipo Y de Roux, con buenos resultados. La realización de cirugía cardíaca compleja, como el by-pass aorto-coronario 51 representó asimismo un impulso para la credibilidad del sistema.…”
Section: Robots Quirúrgicosunclassified